Plight of street children: An explorative study from Varanasi, India - Mona Srivastava; Nasra Shareef (Wolters Kluwer Medknow Publications, 2016)
Rapid pace of unplanned urbanization in the developing countries has resulted in a large proportion of children becoming homeless, leading to multiple children living on the streets. These children are highly vulnerable to exploitation and abuse. Against this background, studies on the situational analysis of street children across India are needed; therefore, a study to assess the condition of street children in the city of Varanasi was planned. Street children registered with a nongovernmental organization were contacted. Four hundred and fifteen children were selected by random sampling, and this group was administered a semi-structured interview containing 35 items. It was found that all forms of abuse were common, but physical abuse (74%) was highest and the police (25.5%) was an important perpetrator. Younger children were much more vulnerable. The sample commonly had boys and between the ages of 10 and 15 years. It was concluded that these children need policies to be incorporated into the mainstream.